The use of in-class debates as a teaching strategy in increasing students’ critical thinking and collaborative learning skills in higher education - Zeta Williams-Brown (Educational Futures, 2015)
This paper will explore the use of debates as an in-class teaching strategy that has the potential to heighten students’ critical thinking and collaborative learning skills. Students undertaking a childhood studies degree had weekly debates that linked media represented topics to theoretical content from their current module. This module covered a range of theoretical and practical perspectives in relation to the child, family and society. Therefore, the topics of weekly debates included the changing nature of childhood, the diversity of family relationships, childhood obesity and the differing ways in which children are socialised. Data was collected using a card-sort and in-class structured interview questions. The study focused on accessing students’ perspectives on the use of these weekly debates. The study found most students held differing, complex perspectives on either the benefit of enhancing collaborative learning or critical thinking skills. The findings suggest that fourteen of the sixteen students in this study did not prefer the use of debates in comparison to other teaching strategies. This is because some students sought more structure in the use of in-class debates to enhance their theoretical understanding. This paper concludes by considering recommendations for the module that include the possibility of using peer-assessment to ensure full student participation.